Developing Professional Competences of Students Through Interactive Training Systems - Khaydarov, Orifjon (Research Parks Publishers, 2025)
This study investigates the effectiveness of interactive training systems in developing professional competences among university students. Through a mixed-methods approach involving 245 participants across different disciplines, we analyzed how various interactive learning technologies impact skill acquisition, professional identity formation, and workplace readiness. Results demonstrate significant improvements in technical proficiency, problem-solving abilities, and soft skills among students exposed to comprehensive interactive training programs. The findings suggest that strategic implementation of interactive systems, when aligned with industry requirements and pedagogical best practices, substantially enhances students' professional development and employability prospects